Possibilities of psychological research by the Internet - Rowiński, Tomasz (Studia Psychologica: Theoria et praxis, 2004)
The article touches certain aspects of conducting on line research and discusses some positives and negatives. The aim of the article is to draw nearer the existing practice and elaborated solutions in this field. The methods presented here allow to conduct reliable on line research emphasizing its ethical aspects. The author tends also to begin a discussion concerning possibilities of conducting on line research. The Internet is an fascinating medium which has impact on many people, even societies. The Net becomes more and more accessible and common. It is a subject to investigate for the researchers. The academicians have a chance to elaborate the standards of on line research.